Multipurpose transformer-type pulse generator; Russian Physics Journal; Vol. 40, iss. 12 - Luchinskii A. V.; Ratakhin N. A. Nikolay Aleksandrovich; Fedushchak V. F.; Shepelev A. N. (1997, 1997)
Title screen